More than Visiting Hours: Maintaining Ties Between Incarcerated Mothers and Their Children - Michalsen, Venezia; Flavin, Jeanne; Krupat, Tanya (Sociology Compass, 2010)
The majority of people in America’s prisons are the parents of minor children. Incarcerated mothers, in particular, were likely to have been a part of their children’s lives before their imprisonment, and most will soon be returning to the community and to their children. Research has shown that it is in the best interests of the mothers and the children to maintain a relationship across the prison bars. In this article, we use the example of New York State to show how institutional policies and structures can impede or encourage efforts to maintain ties between women and their children and why demonstrating support for family ties must extend well beyond having visiting hours.
Keywords: dept.soc; peer-reviewed

Book Review: Black Woman’s Burden: Commodifying Black Reproduction - Jackson, Shirley A. (Contemporary Sociology, 2010)
Keywords: book.review; dept.soc

Book Review: women: judith schoenen, das image der frau — wege zu einem neuen selbstbild [A woman’s image — path to a new Self-Portrait]. opladen and farmington hills, MI: barbara budrich, 2008, 172 pp., ISBN 9783866491007, 12.90 - Eich-Krohm, Astrid (International Sociology, 2010)
Keywords: book.review; dept.soc